Problematika Penerapan Asas Dominus Litis: Urgensi Pemberian Nasihat Hakim terhadap Cacat Formil Surat Kuasa: (Studi Putusan No. 14/Pdt.G/2025/PN Kba) - Natasya Dwi Nanda; Sindy Arzety; Anggi Sri Haryanti Simarmata (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
This research is prompted by legal complications within civil procedural law, specifically regarding the failure of judges to identify formal defects in special powers of attorney during the preliminary stages of trial. The central focus of this study examines Decision Number 14/Pdt.G/2025/PN Kba, in which a lawsuit was declared inadmissible (Niet Ontvankelijke Verklaard) only after a seven-month litigation process that had already progressed through evidentiary hearings and local inspections. The objective is to evaluate the effectiveness of the dominus litis principle in empowering judges to provide procedural guidance for lawsuit amendments, while testing its alignment with the principles of simple, fast, and low-cost justice. Employing a normative legal research method with statutory and case-based approaches, the legal materials are analyzed qualitatively using the legal syllogism technique. The findings indicate that the application of the dominus litis principle in the a quo case remains ineffective due to the judges' passive and formalistic tendencies. Such an approach neglects the ex-officio authority mandated under Articles 119 and 132 of the HIR. This ineffectiveness results in significant judicial inefficiency, causing undue loss of time and financial resources for justice seekers. Consequently, this study recommends strengthening rigorous initial screening mechanisms by the panel of judges at the first hearing. This preventive measure is essential to curb the waste of judicial resources and ensure the realization of substantial justice for all disputing parties.